1999
DOI: 10.1073/pnas.96.4.1574
|View full text |Cite
|
Sign up to set email alerts
|

Multinuclear solid-state three-dimensional MRI of bone and synthetic calcium phosphates

Abstract: Multinuclear three-dimensional solid-state MRI of bone, tooth, and synthetic calcium phosphates is demonstrated in vitro and in vivo with a projection reconstruction technique based on acquisition of free induction decays in the presence of fixed amplitude magnetic field gradients. Phosphorus-31 solid-state MRI provides direct images of the calcium phosphate constituents of bone substance and is a quantitative measurement of the true volumetric bone mineral density of the bone. Proton solid-state MRI shows the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 26 publications
1
71
0
1
Order By: Relevance
“…34 In principle also other MR approaches have potential to visualize repaired bone lesions like the use of 19 F nuclei in contrast material 35 or the application of 31 P MR to differentiate between natural and synthetic hydroxyapatite. 36 In conclusion, this study reported on the first in vivo MRI of a CPC repaired lesion in bone, using a ZTE acquisition sequence and clinically approved Gd-DTPA for enhanced contrast. This offers a novel radiation-free method to visualize CPC degradation and bone regeneration in preclinical experiments.…”
Section: Discussionmentioning
confidence: 99%
“…34 In principle also other MR approaches have potential to visualize repaired bone lesions like the use of 19 F nuclei in contrast material 35 or the application of 31 P MR to differentiate between natural and synthetic hydroxyapatite. 36 In conclusion, this study reported on the first in vivo MRI of a CPC repaired lesion in bone, using a ZTE acquisition sequence and clinically approved Gd-DTPA for enhanced contrast. This offers a novel radiation-free method to visualize CPC degradation and bone regeneration in preclinical experiments.…”
Section: Discussionmentioning
confidence: 99%
“…13 C MR spectroscopy (as in Fig. 6) has already found multiple applications in archaeological research (Lambert et al, 2000), and 31 P MRI has been applied to fresh bone and teeth (Li, 1991;Wu et al, 1999).…”
Section: Perspectives For Fossil Mrimentioning
confidence: 99%
“…Consequently, images of cortical bone must be acquired using solid-state imaging techniques to detect the 31 P nuclei immobilized in the inorganic matrix (15)(16)(17)(18)(19) or the 1 H nuclei in bone water (20,21). In mineralizing systems, the tissues are still mostly hydrated and the reduction in the water proton signal can be attributed to the displacement of water by mineral deposits containing few mobile protons, and thus proton images of tissue water can be inversely related to its mineral content (12).…”
Section: Introductionmentioning
confidence: 99%